Pituitary–Adrenal Responses and Glucocorticoid Receptor Expression in Critically Ill Patients with COVID-19 - Dimitra A. Vassiliadi (MDPI AG, 2021)
The hypothalamus–pituitary–adrenal (HPA) axis was described as the principal component of the stress response 85 years ago, along with the acute-phase reaction, and the defense response at the tissue level. The orchestration of these processes is essential since systemic inflammation is a double-edged sword; whereas inflammation that is timely and of appropriate magnitude is beneficial, exuberant systemic inflammation incites tissue damage with potentially devastating consequences. Apart from its beneficial cardiovascular and metabolic effects, cortisol exerts a significant immunoregulatory role, a major attribute being that it restrains the excessive inflammatory reaction, thereby preventing unwanted tissue damage. In this review, we will discuss the role of the HPA axis in the normal stress response and in critical illness, especially in critically ill patients with coronavirus disease 2019 (COVID-19). Finally, a chapter will be dedicated to the findings from clinical studies in critical illness and COVID-19 on the expression of the mediator of glucocorticoid actions, the glucocorticoid receptor (GCR).